Quelle serait la quantité d’informations nécessaire et suffisante pour une définition ? - Alic, Liliana (Studia Romanica Posnaniensia, 2012)
In this paper we intend to prove the importance of cognition in the difficult and complex task of finding the right definition for a term or a collocation. The principles of categorization can be successfully applied in order to find the needed and structured information about the perceived world. They can also help finding the attributes that distinguish representatives of one category. Categorizing by using prototypes contributes to the development of individuals’ vocabulary in various fields and also in discovering the most important distinctive features in order to define object, beings or abstract notions of the perceived world. A good definition must contain not only distinctive features but also specific attributes, in order to increase its accuracy.